2019
DOI: 10.3390/su11061694
|View full text |Cite
|
Sign up to set email alerts
|

Technology Spillover Effect in China: The Spatiotemporal Evolution and Its Drivers

Abstract: Under the background of global economic integration, the technology spillover effect is playing a more and more important role in the technological progress of developing countries. In this circumstance, this paper conducted an in-depth analysis on the 12-year spatial-temporal evolution of the international technology spillover effect and its driving determinants in China during the period of 2003 to 2014. Analytical results highlighted that: (1) As a whole, the international technology spillover effect in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Moreover, Liu [15] took Chinese high-tech firm as the research object, researching the spillover effect of multinational firm in host, it is found that high-tech acceptance level is helpful to improve the technology of high-tech firm, but firm development also needs strong innovation ability. Similarly, Liu [2] also came to a similar conclusion. From the viewpoint of Benjamin [16], it is certain that both formal and informal associations can adjust the core management ability through spillover effect, and then exert a positive effect on innovation ability.…”
Section: Literature Reviewsupporting
confidence: 57%
See 4 more Smart Citations
“…Moreover, Liu [15] took Chinese high-tech firm as the research object, researching the spillover effect of multinational firm in host, it is found that high-tech acceptance level is helpful to improve the technology of high-tech firm, but firm development also needs strong innovation ability. Similarly, Liu [2] also came to a similar conclusion. From the viewpoint of Benjamin [16], it is certain that both formal and informal associations can adjust the core management ability through spillover effect, and then exert a positive effect on innovation ability.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Technological breakthrough of scientific research units (TBASRU) is the strong foundation of firm innovation; Laboratory technology controllability (LTIC) refers to the ability to control innovation in the LTI stage, that is, the possibility of the initial intention turning into the final intention [36,37,43,44]. LTI willingness (LTIW) shown in Equation (2).…”
Section: Simulation Model and Variables Codementioning
confidence: 99%
See 3 more Smart Citations